2021
DOI: 10.3390/su13052924
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Causal Relationships among Carbon Emissions, Economic Growth, and Life Expectancy in Turkey: Evidence from Time and Frequency Domain Causality Techniques

Abstract: It is not a gainsaying that challenges to both healthy living and the environment are the result of deteriorating environmental quality with the attendant effect on environmental sustainability. To provide a solution to the issue, our study uses long time-series data from 1960 to 2018, and employs an overlapping generational model, the Bayer–Hanck cointegration test, wavelet coherence, Fourier Toda–Yamamoto, and Breitung–Candelon frequency-domain spectral causality tests to investigate the causal relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Studies conducted by Sharma (2018) and Biyase & Maleka (2019) found that life expectancy, democracy, and the population had the expected positive impact on economic growth. The study by Cervellati & Sunde (2011);Rjoub et al (2021); Ngangue & Manfred (2015), and He & Li (2019) found a positive movement between life expectancy and economic growth in a study in several developed and developing countries (Bashir et al, 2019). The results are robust to address the possible reverse causality between life expectancy and economic growth.…”
Section: Introductionmentioning
confidence: 75%
“…Studies conducted by Sharma (2018) and Biyase & Maleka (2019) found that life expectancy, democracy, and the population had the expected positive impact on economic growth. The study by Cervellati & Sunde (2011);Rjoub et al (2021); Ngangue & Manfred (2015), and He & Li (2019) found a positive movement between life expectancy and economic growth in a study in several developed and developing countries (Bashir et al, 2019). The results are robust to address the possible reverse causality between life expectancy and economic growth.…”
Section: Introductionmentioning
confidence: 75%
“…Several authors have investigated the relationship between life expectance and different forms of air pollution, including carbon emission. Very few authors like that of Rjoub et al . (2021) have discovered positive linear relationship between carbon emission and life expectancy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2021) have discovered positive linear relationship between carbon emission and life expectancy. Rjoub et al. (2021) investigated the causal relationships between carbon emissions, economic growth and life expectancy in Turkey for the period from 1960 to 2018 using an overlapping generational model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in most quantiles, the impact of economic growth on carbon dioxide emissions is negative. Rjoub et al [4] explored the relationship between carbon emissions, life expectancy, and economic growth in Turkey from the perspective of energy consumption, human health, and environmental hazards. Odhiambo [5] discussed the relationship between carbon emissions and economic growth in South Africa and found that energy consumption plays a positive role in promoting carbon emissions and economic growth.…”
Section: Introductionmentioning
confidence: 99%